Use of radiographic and histologic scores to evaluate cats with idiopathic megacolon grouped based on the duration of their clinical signs - Abdelbaset-Ismail, Ahmed; Ibrahim, Nehal; Sobh, Mohammed S.; Ahmed, Ahmed Ezzat; Al-Saeed, Fatimah A.; Al-Doaiss, Amin A.; Al Syaad, Khalid M.; Elmezyen, Abd-Elmegeed; Abd-Elmaboud, Mahmoud (Frontiers in Veterinary Science, 2022)
The main objective of this study was to determine whether duration of clinical signs of idiopathic megacolon in cats affected their diagnosis and prognosis after treatment. Medical records of cats that either had confirmed megacolon for an unknown cause (cat patients) or with normal bowels (control cats) were reviewed. Cat patients were grouped based on the duration of their clinical signs (constipation/obstipation) to cats <6 months and ≥6 months. For all feline patients, abdominal radiographs (for colonic indexes) and resected colon specimens (for histology) were assessed versus control cats. Treatment applied to cat patients was also evaluated. Cat patients were older (p = 0.0138) and had a higher MCD (mean 41.25 vs. 21.67 mm, p<0.0001) and MCD/L5L ratio (1.77 vs. 0.98, p<0.0001) than controls. Compared to cats with <6 months, cats ≥6 months showed a higher MCD (43.78 vs. 37.12 mm, p<0.0001) and MCD/L5L ratio (1.98 vs.1.67, p<0.0001). Histologically, increased thickness of the smooth muscularis mucosa (54.1 vs. 22.33 µm, p<0.05), and inner circular (743.65 vs. 482.67 µm, p<0.05) and outer longitudinal (570.68 vs. 330.33 µm, p<0.05) smooth muscular layers of the muscularis externa was noted only in cat patients with ≥6 months compared to controls. Similarly, fewer ganglion cells (0.93 vs. 2.87, p<0.005) and more necrosed myocytes (2.25 vs. 0.07, p<0.005) were observed in cats with ≥6 months. In contrast to <6 months, majority of cats (94.4%) with ≥6 months duration did not show any response to medical treatment, and therefore underwent surgery with favorable results. In conclusion, this study suggests that the duration of clinical signs should be considered in conjunction with maximal colon scores to evaluate cats for idiopathic megacolon and determine the level of treatment. Functional abnormalities of the colonic smooth muscles may be a possible cause of idiopathic megacolon in cats.